Integrating a Love-Based Curriculum into Islamic Religious Education for Character Development in the Digital Era: An Integrative Literature Review - Riskiyah; Abdul Aziz; Ayus Ahmad Yusuf (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study examines the integration of a Love-Based Curriculum into Islamic Religious Education as a framework for strengthening student character in the digital era. Employing an integrative literature review design, the study synthesized scholarly articles, books, book chapters, conference proceedings, and educational policy documents published between 2010 and 2026. Relevant literature was systematically collected from Scopus, Web of Science, ERIC, DOAJ, Google Scholar, Garuda, and SINTA and analyzed through thematic synthesis involving open coding, axial coding, categorization, and conceptual interpretation. The findings indicate that mahabbah (love), rahmah (compassion), and amanah (trustworthiness) function not only as moral outcomes but also as pedagogical mechanisms that facilitate character formation through caring educational relationships, reflective learning, ethical guidance, and value internalization. The literature further suggests that deep learning, digital ethics, and collaboration among schools, families, and communities strengthen students’ moral resilience and responsible participation in digitally mediated environments. The originality of this study lies in integrating pedagogical love, Islamic educational philosophy, deep learning, and digital ethics into a unified conceptual framework for character development. This study contributes to contemporary Islamic education by offering a humanistic and spiritually grounded model that balances intellectual competence, ethical responsibility, emotional maturity, and moral resilience in response to the challenges of digital transformation.